Pengaruh Strategi Pembelajaran Contextual Teaching And Learning (CTL) Terhadap Hasil Belajar Siswa Pendidikan Agama Kristen Dan Budi Pekerti Kelas VIII SMP N 1 Tarutung Tahun Pelajaran 2023/2024 - Andriani Peronika Sinaga; Taripar Aripin Samosir; Robinhot Sihombing; Limmarten Simatupang; Grecetinovitria M. Butar-Butar (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The aim of this research is to prove the significant influence of the Contextual Teaching and Learning (CTL) Learning Strategy on the Learning Outcomes of Class VIII Christian Religious Education and Character Education Students at SMP N 1 Tarutung for the 2023/2024 Academic Year. The method used in this research is a quantitative experimental method. The population was all students in class VIII of SMP N 1 Tarutung for the 2023/2024 academic year, totaling 157 people and a sample of 32 people were determined who were chosen deliberately (purposive sampling). Data was collected with 30 test items. The results of data analysis show that the learning outcomes of students taught with the Contextual teaching and Learning (CTL) Learning Strategy are higher than the Learning Outcomes of students taught with Conventional Strategies in Christian Religious Education and Character Education Subjects Class VIII SMP N 1 Tarutung Academic Year 2023/ 2024. Data analysis using the t test obtained a tcount value = 2.414 while the ttable value for error was 5% and n1 + n2 – 2 = 62, namely 1.998. So the ratio obtained is tcount > ttable, namely 2.414 > 1.998. Thus H0 is rejected, because H0 is rejected then H1 is accepted.